Public ICT investment in reaction to the economic crisis: A case study on measuring IT-related intangibles in the public sector - Marianne Saam; Laura Weinhardt; Lukas Trottner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
In this paper, we (1) analyse the German public IT-spending programme 2009-11 adopted after the crisis in terms of its tangible vs. intangible asset creation, (2) consider this relatively well-described programme as a use case for categorising IT-related intangibles in government beyond software (including e.g., IT-training, innovation in e-services), (3) investigate how to form insightful aggregates of intangible IT-related investment from project level data and, in comparison, from the regular public budget in Germany. Based on project descriptions, we find out that half of the spending was on IT security-related projects. According to our estimations based on quantitative information, qualitative information and approximations, about half of the total spending was on intangibles, of which again about half went into software and a quarter into consulting. As a new output-based category for some assets created in the programme, we propose the category "concepts".
urn:nbn:de:bsz:180-madoc-417586
Keywords: 330; Public Sector; IT Investment; Intangible Assets; E-Government